Leadership in early childhood education: case studies of Indonesian public kindergartens - Rubiyantoro, Yohan (2024)
Over the past three decades, studies of leadership in early childhood education have increased worldwide. However, only limited research has been conducted in Southeast Asia. Therefore, this gap provides a warrant for my research into early childhood leadership in Indonesia, an area of knowledge that has been underexplored. This current study focused on early childhood leadership at the kindergarten level. The research examines the nature of leadership in selected public kindergartens in Indonesia. It also examines the perceived purposes of kindergarten education, how leadership is implemented, kindergarten organisational structure, curriculum development, and the relationship between kindergarten leaders and parents. This study also considers how kindergarten leaders responded to the Covid-19 pandemic, which emerged as a theme during the data collection process. This is an exploratory multiple case study, involving semi-structured interviews, and documentary analysis from different contexts and regions in Indonesia. Due to the pandemic, study participants were interviewed online in four main regions: the capital (Jakarta), the central part (Bali), the western part (North Sumatra), and the eastern part (South Sulawesi). Participants in this study include kindergarten heads, teachers, teaching assistants, administrative assistants, parents, and local education offices. The study involved a total of 40 participants. This study found that ECE leadership in Indonesia is problematic in several respects, starting with the principal selection process, where political interests dominate. Heads feel overburdened with administrative tasks and also lack training. This research found that public kindergartens follow a similar top-down hierarchy. Principals interpret the curriculum as a central government-given policy, with little autonomy in its implementation. During the Covid-19 pandemic, kindergarten leaders faced extreme pressure and it also disrupted teaching and learning. The thesis outlines the implications for policymakers, principals, teachers, and for further research. It recommends that central government should reevaluate the selection process for public kindergarten principals. It also recommends that the government should improve leadership training for future principals and reduce their administrative burden